Familial left ventricular noncompaction cardiomyopathy due to a novel mutation in the MYH 7 gene - Sujata S Alawani; AbrahamPaul; Mani Ram Krishna; HishamAhamed (Wolters Kluwer Medknow Publications, 2021)
Left Ventricular Non Compaction (LVNC) is considered a unique cardiomyopathy according to the American Heart Association guidelines. The genetic ethology of LVNC in children is not completely understood although upto 41% of LVNC are thought to be genetic. We report a family with LVNC due to a novel mutation in the MYH 7 gene.